2022
DOI: 10.1186/s12885-021-09115-6
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint inhibitors in metastatic gastric and GEJ cancer: a multi-institutional retrospective analysis of real-world data in a Western cohort

Abstract: Background Safety and efficacy of immune checkpoint inhibitors in advanced gastric or gastroesophageal junction (GEJ) cancer could be demonstrated in predominantly Asian cohorts, whereas data in Western patients outside of clinical trials are vastly missing. Methods In this multi-institutional retrospective analysis conducted at nine oncologic centers in Austria, we tried to assess feasibility of checkpoint inhibitors in advanced gastric/GEJ cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In this case, the tumor microsatellite has been stable, a different finding from most previous studies. Additionally, it has been demonstrated that microsatellite status had no significant effect on median progression-free survival (PFS) ( 35 , 39 , 40 ). The ECOG PS 1 in our case confirmed that the prognosis of patients with a PS of ≤1 is better than in those with a PS of ≥2 ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the tumor microsatellite has been stable, a different finding from most previous studies. Additionally, it has been demonstrated that microsatellite status had no significant effect on median progression-free survival (PFS) ( 35 , 39 , 40 ). The ECOG PS 1 in our case confirmed that the prognosis of patients with a PS of ≤1 is better than in those with a PS of ≥2 ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been demonstrated that microsatellite status had no significant effect on median progression-free survival (PFS) ( 35 , 39 , 40 ). The ECOG PS 1 in our case confirmed that the prognosis of patients with a PS of ≤1 is better than in those with a PS of ≥2 ( 40 ). In contrast, it has been reported that for GC PD-L1-negative patients with high-efficiency mismatch repair (PMMR)/MSS and TMB-1, immune checkpoint blockade can also achieve good outcomes after systematic treatment failure ( 41 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the recent years of checkpoint inhibitors, both pembrolizumab and nivolumab have also shown survival benefits in metastatic gastric carcinoma. Cytotoxic chemotherapy, combined with trastuzumab and pembrolizumab, is now recommended as the standard of care forfirst-line therapy formetastatic gastric carcinoma [2].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been demonstrated that microsatellite status had no significant effect on median progression-free survival (PFS) (35,39,40). The ECOG PS 1 in our case confirmed that the prognosis of patients with a PS of ≤1 is better than in those with a PS of ≥2 (40). In contrast, it has been reported that for GC PD-L1-negative patients with highefficiency mismatch repair (PMMR)/MSS and TMB-1, immune checkpoint blockade can also achieve good outcomes after systematic treatment failure (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%